Orthogonal tight binding model for silicon carbide - Kamenski, P (2011)
A new orthogonal tight binding (OTB) model for the silicon carbide (Si-C) system is presented. The model is parameterized in the reduced TB form which provides a critical step towards the development of an analytic bond-order potential (BOP) for Si-C. Coarse-grained from density functional theory (DFT), through TB, analytic BOPs address a number of the deficiencies of current interatomic potentials for Si-C including the neglect of explicit π-bonding and more accurate σ-bond contributions. Furthermore, the new reduced OTB model is important within TB in its own right as the first simple, selfconsistent OTB model parameterized specifically for SiC without the use of any averaging of elemental interactions. Selfconsistency is achieved through local charge neutrality (LCN). The distance-dependent functions used to define the Hamiltonian matrix elements in the two-centre approximation were obtained directly from given DFT-projected data, and repulsive parameters were fit to DFT binding energies. The electronic structure, binding energies, and heat of formation for the groundstate structures are reproduced well with no spurious groundstate structures found in a database of over 200 unique crystal structures. The significant improvements over existing OTB models for elemental Si and C and the binary SiC results show good promise for further applicability in modelling a wide range of phenomena in Si-C such as thin film growth or interfaces in general.